Assessment of faecal glucocorticoid metabolite excretion in captive female fishing cats (Prionailurus viverinus) in Thailand - Jaruwan Khonmee (2018)
© The Author 2016. There is little information on the endocrinology of fishing cats (Prionailurus viverinus), an endangered species in Southeast Asia, especially that pertaining to adrenal function. This study characterized faecal glucocorticoid metabolites in female fishing cats housed at Chiang Mai Night Safari to investigate seasonal and age relationships in hormone patterns. Faecal samples were collected 3 days/week for 1 year from seven females ranging in age from 4.5 to 9.6 years. A corticosterone enzyme immunoassay was validated for fishing cats by showing increases (~60%) in faecal glucocorticoid immunoactivity above pre-treatment baseline levels within 1-2 days after an adrenocorticotrophic hormone injection. Faecal glucocorticoid metabolite concentrations were not related to age (P > 0.05), but there was a seasonal effect, with concentrations being higher (P < 0.05) during the winter (1.54 ± 0.04 μg/g) and rainy season (1.43 ± 0.04 μg/g) compared with the summer (1.22 ± 0.05 μg/g). Significant relationships were found between faecal glucocorticoids and rainfall (positive) and day length (negative), but not a temperature-humidity index. This is the first study to assess adrenal steroidogenic activity in female fishing cats, and we found that glucocorticoid metabolite production was influenced by seasonal factors, but not by age. We conclude that weather patterns should be taken into consideration in future studies of glucocorticoid activity in this endangered species, especially those studies aimed at improving captive management to create self-sustaining and healthy populations.